PP.29.09: HYPERTENSION AND DIABETES PREVALENCE AND MANAGEMENT IN PORTUGAL. (June 2015) - Macedo, M.; Ferreira, R.
Abstract : Objective: Hypertension is the leading risk factor contributing for the cardiovascular morbidity and mortality in the Portuguese population. However its association with diabetes is very frequent and synergistically increase cardiovascular risk in these patients. It's management is predominantly undertaken by primary physicians. Estimates of the prevalence, treatment and control of Blood Pressure (BP) in the primary care patients with diabetes, are needed to adequately address the high burden of hypertension and diabetes in Portugal. Design and method: A retrospective analysis of patient-based electronic medical records was conducted during the year of 2013. To examine the effect of regular General practitioner (GP) management and control on BP across at least two annual visits. A subgroup of patients with elevated BP and ageequal or more than 18 years old and diabetes, were selected in a total of 528 242 patients (51, 5 % women). Hypertension was defined as Systolic BP and or Diastolic BP equal or more than 140/90 mmHg. Results: The overall prevalence of hypertension and diabetes was 20, 0% (men 23, 1% and women 17, 8%). Among those patients under hypertensive treatment, the control rates were 23, 7% (men 28, 7% and women 20, 5%). The main classes of antihypertensive prescribed were tiazide diuretics 30, 2% (men 23, 7% and women 29, 7%), beta-blockers 27, 1% (men 26, 5% and women 27, 4%), calcium channel blockers 22, 4% (men 21, 1% and women 19, 5%); ECAI 26, 5% (men 24, 5%, women 21, 7%) and AII antagonists 46, 9% (men 47, 9% %, and women 42, 3 %). Conclusions: The prevalence of hypertension with hypertension was lower than in other studies. Arterial blood pressure control was very poor, only four out of ten in the subgroup of Portuguese patients aged 18 years or older with diabetes. Blood pressure control assessment was significantly better in men. A more intensive approach in the management of the BP in primary care is required to ensure that more patients achieve BP control targets.